1998
DOI: 10.1007/bf03217120
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitudes towards mathematics in single-sex and coeducational schools

Abstract: This paper examines students' attitudes towards mathematics at the secondary school level. Using five of the Fennema-Sherman scales, the attitudes of boys and girls in Grades 8 to 12 in four schools were compared: a single-sex boys" and a single-sex girls' private school, and a state and a private coeducational school. Multivariate analysis of variance was used to guide an exploration of how students' attitudes varied according to grade, sex and educational setting. There were no differences between students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…This pattern was repeated with a sample of grade 10 and 11 students , and with grades 6 to 8 students (Fennema & Sherman, 1978). Some years later, similar findings were reported by Tartre and Fennema (1995) in a longitudinal study of students as they progressed through grades 6 to 12, by Yong (1992) with gifted African-American middle grade students, and among Australian grade 7 (Forgasz, 1995) and grade 8 to 12 students (Norton & Rennie, 1998). Comparable findings have also been reported in many international studies in which the mathematics as a male domain subscale or other similar measures were used (e.g., Birenbaum & Kraemer, 1992;Boswell, 1985;Cheung, 1988;KaiserMessmer, 1993;Lummis & Stevenson, 1990;Otten & Kuyper, 1988;Tocci & Engelhard, 1991;Visser, 1988).…”
Section: Stereotyping Mathematics As a Male Domainsupporting
confidence: 61%
“…This pattern was repeated with a sample of grade 10 and 11 students , and with grades 6 to 8 students (Fennema & Sherman, 1978). Some years later, similar findings were reported by Tartre and Fennema (1995) in a longitudinal study of students as they progressed through grades 6 to 12, by Yong (1992) with gifted African-American middle grade students, and among Australian grade 7 (Forgasz, 1995) and grade 8 to 12 students (Norton & Rennie, 1998). Comparable findings have also been reported in many international studies in which the mathematics as a male domain subscale or other similar measures were used (e.g., Birenbaum & Kraemer, 1992;Boswell, 1985;Cheung, 1988;KaiserMessmer, 1993;Lummis & Stevenson, 1990;Otten & Kuyper, 1988;Tocci & Engelhard, 1991;Visser, 1988).…”
Section: Stereotyping Mathematics As a Male Domainsupporting
confidence: 61%
“…Findings of reported high mathematics self-confidence amongst girls in single-sex schools confirm earlier studies (Belcher et al 2006;Eshun 2004;Mallam 1993;Nyala 2010;Rowe 1988). These findings also support those other studies that have found no difference in boys and girls in single-sex schools (Brown and Ronau 2012;Signorella et al 2013) but contradict studies showing higher self-confidence amongst boys in single-sex schools (Githua and Mwangi 2003;Norton and Rennie 1998). The literature supports comparable levels of mathematics confidence among both sexes in coed schools (e.g., Norton and Rennie 1998) but does not support the findings of Asante (2012) and McGraw et al (2006).…”
Section: Differences On the Vom Constructssupporting
confidence: 74%
“…This paper begins with Schoenfeld (1985, p. 44) notion that "belief is one's mathematical worldview". Self-beliefs such as self-confidence and self-concept in mathematics learning have for some time consistently emerged as an important variate in sex-related differences in mathematics (Belcher et al 2006;Marsh et al 2013;Norton and Rennie 1998). In this paper, self-concept is defined in line with Purkey (1970) and Rosenbergʹs (1986) notion of self-concept as the totality of a complex, organized, and dynamic system of beliefs, attitudes and opinions that each individual holds, having reference to himself as the object.…”
Section: Self-beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fisher and Rickards (1998) found that students' attitude towards mathematics tended to be more positive in classroom where students perceived greater leadership and helping/friendly behaviors in their teachers, and more negative in their classrooms where students perceived their teachers as admonishing and enforcing strict behaviors. Other researchers have compared the effect of separate (single-sex) and coeducational classrooms upon students' attitude (Norton and Rennie, 1998).…”
Section: Introductionmentioning
confidence: 99%